Design of Service Information System as A Strategy for Implementing Knowledge Management in Zakat Management Organizations (A Case Study at Baitul Maal, Islamic University of Bandung) - Adhi Dwinata; Suwarsi, Sri; Oktini, Dede R. (Journal of Information System, Technology and Engineering, 2025)
The Baitul Maal Unisba (BMU) organization faces obstacles in the form of suboptimal service so that researchers have initiated improvements to the website-based information system and make the information system a knowledge management strategy at the BMU institution. This study aims to provide an overview of the design of a better information system and utilize the information system that has been designed as a knowledge management strategy. Qualitative methods with a case study approach have been used in this study. The results of the study indicate that the design of a better service information system with reference to the evaluation results is carried out using the WordPress service at the address www.baitulmaalunisba.wordpress.com. The design can then be utilized in the knowledge management (KM) implementation plan in the BMU organization, namely as a form of codification strategy and as a technology component at the combination stage. To realize this, the website manager uploads knowledge content, adds special KM features to the website content section, encourages organizational human resources to read and respond to the knowledge content that has been uploaded and improves the search feature on the website to make it easier for website visitors to access information and knowledge.